2021
DOI: 10.1364/oe.435632
|View full text |Cite
|
Sign up to set email alerts
|

Generation of annular femtosecond few-cycle pulses by self-compression and spatial filtering in solid thin plates

Abstract: Annular-shaped femtosecond few-cycle pulses are generated by 40fs laser pulses propagating through 6 solid thin plates in numerical simulations as well as in experiments. The generation of such pulses takes advantage of the conical emission caused by plasma effect, which introduces continuously varying off-axis plasma density along the radial direction of the propagating beam. The negative dispersion induced by the plasma causes the pulse at particular radial location to be self-compressed and to form an annul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The only report on soliton self-compression using Ti: sapphire laser is by Travers et al [32] They reported the soliton self-compression in the hollow-core capillaries by applying shorter pump pulses and longer HCF. They achieved the short- Self-compression by filamentation [ 28,45,48,73,[75][76][77]79,81,84,86] Self-compression by ionization [ 26,40,41,69,74,83,85] I in < I th Self-compression by self-focusing [ 25,35] Self-compression by solitons [ 32,39,42,51,61,62,65,66,70,78,80] est compressed pulse of all works which is only 1.2 fs wide. We can see that only soliton self-compression can reach very short pulse durations (<5 fs), although their pulse energy tends to be relatively small.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The only report on soliton self-compression using Ti: sapphire laser is by Travers et al [32] They reported the soliton self-compression in the hollow-core capillaries by applying shorter pump pulses and longer HCF. They achieved the short- Self-compression by filamentation [ 28,45,48,73,[75][76][77]79,81,84,86] Self-compression by ionization [ 26,40,41,69,74,83,85] I in < I th Self-compression by self-focusing [ 25,35] Self-compression by solitons [ 32,39,42,51,61,62,65,66,70,78,80] est compressed pulse of all works which is only 1.2 fs wide. We can see that only soliton self-compression can reach very short pulse durations (<5 fs), although their pulse energy tends to be relatively small.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The emergence of ultrashort pulse laser technology 21–26 offers an excellent strategy for studying this problem. Ultrashort lasers use extremely short periods of light exposure, 27–29 providing an unprecedented shutter speed for photographing the motion of microscopic particles, 30–34 where, the shorter the pulse width of the laser pulse, the faster the shutter speed. Thus, generating shorter laser pulses has become an important aspect of ultrafast science 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to self-compression involves conical radiation generated from a laser-induced plasma, capitalizing on the negative dispersion properties of the plasma medium. Gao et al reported the self-compression of an 800 nm pulse from 40 fs down to 8.8 fs using conical radiation from multiple thin plates [37]. In their experiment, negative dispersion in the laser-induced plasma played a crucial role in achieving the pulse compression.…”
mentioning
confidence: 99%
“…This negative index gradient leads also to negative linear group velocity dispersion within the plasma channel, causing the leading edge of the pulse to travel slower than the trailing edge and resulting in temporal compression of the pulse. Subsequently, the balance between the group velocity dispersion due to SPM and plasma leads to the self-compressed pulses in the conical radiation [37]. Our experimental setup consists of only three key optical components and utilizes conical radiation generated by a tightly focused laser beam, eliminating the need for additional dispersion compensation elements.…”
mentioning
confidence: 99%